2021
DOI: 10.1007/s13364-021-00564-9
|View full text |Cite
|
Sign up to set email alerts
|

Spatial ecology of the stone marten in an Alpine area: combining camera-trapping and genetic surveys

Abstract: A species’ potential distribution can be modelled adequately only if no factor other than habitat availability affects its occurrences. Space use by stone marten Martes foina is likely to be affected by interspecific competition with the strictly related pine marten Martes martes, the latter being able to outcompete the first species in forested habitats. Hence, to point out the environmental factors which determine the distribution and density of the stone marten, a relatively understudied mesocarnivore, we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 82 publications
(84 reference statements)
0
5
0
Order By: Relevance
“…In the Lepontine Alps, where pine marten occurrence was negligible (see also Balestrieri et al, 2021), the proportional contribution of protein energy to stone marten's diet did not differ from pine martens'. The only other study which, to our knowledge, investigated the diets of both martens in an area where the stone marten was dominant in terms of relative abundance was carried out in northern Portugal, at the southwestern limit of pine marten distribution (Monterroso et al, 2016).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In the Lepontine Alps, where pine marten occurrence was negligible (see also Balestrieri et al, 2021), the proportional contribution of protein energy to stone marten's diet did not differ from pine martens'. The only other study which, to our knowledge, investigated the diets of both martens in an area where the stone marten was dominant in terms of relative abundance was carried out in northern Portugal, at the southwestern limit of pine marten distribution (Monterroso et al, 2016).…”
Section: Discussionmentioning
confidence: 90%
“…With the aim of comparing the diets of pine and stone martens in mountain areas of either sympatry or allopatry, we (1) carried out an extensive genetic survey for marten scats in the western Italian Alps in 2019 (Figure 1c) and (2) analyzed genotyped fecal samples collected in NE Piedmont in 2015–2017 (Figure 1a,b), as part of a study aimed at assessing the distribution of mustelids in the Val Grande National Park and neighboring areas (Lepontine Alps; Balestrieri et al, 2018). In the first area both martens are known to occur (based on museum archives and records collected in the period 1990–2010; Sindaco & Carpegna, 2010), while the pine marten is suspected to have recolonised the latter area only in the last decade (Balestrieri et al, 2021). Following Remonti et al (2016) the estimated volumes of food items used by both martens were then transformed in macronutrient energy ratios to allow the sound comparison of their feeding requirements (Gazzola & Balestrieri, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Probably owing to the challenges involved in their individual identification, stone marten density estimates are lacking in the literature. Exceptions include Balestrieri et al (2021), who estimated 0.95 (0.7 – 1.3) individuals/km 2 in the Alpine areas of N Italy using the R package capwire (Pennell et al, 2013). To the best of our knowledge, only two studies reported stone marten density in Mediterranean region of Iberia, both in places of Extremadura (SW Spain) and estimated trueD̂=0.24;SD:0.08$$ \hat{D}=0.24;\mathrm{SD}:0.08 $$ and trueD̂=0.26;SD:0.14$$ \hat{D}=0.26;\mathrm{SD}:0.14 $$ individuals/km 2 for Valdecigüeñas (Jiménez et al, 2017) and Matachel Valley (Jiménez, Nuñez‐Arjona, et al, 2019), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Between September 2021 and February 2022, we collected 30 samples per area, selecting fresh-looking faeces to obtain amplifiable, non-degraded DNA. Following Ebert et al 57 , sample size for genetic analysis was calculated as 2.5-3 times the "assumed" number of foxes in each population and based on expected genotyping success (50%, average of previous studies [58][59][60] ). The assumed number of foxes was assessed using available home range sizes for Alpine areas (358 ha) 46 .…”
Section: Sampling Methodsmentioning
confidence: 99%